1995
DOI: 10.1128/iai.63.3.884-890.1995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transferrin-binding protein 2 within the transferrin-binding protein complex as a potential antigen for future meningococcal vaccines

Abstract: Because the meningococcal transferrin receptor was shown to elicit bactericidal and protective antibodies in laboratory animals, we undertook a study of the protective role of each of the polypeptides within the Tbp1-Tbp2 complex. We developed a procedure to purify from Neisseria meningitidis B16B6 the two proteins in milligram amounts and raised specific antisera in rabbits and mice. Only antisera specific for Tbp2 displayed bactericidal activity against the parent strain. Mice immunized with purified Tbp2 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 49 publications
3
38
0
2
Order By: Relevance
“…The interaction between isolated meningococcal Tbps and hTF has been quantitatively characterized for the first time. This has been possible for individual TbpA and TbpB due to the development of a novel purification procedure which preserved the hTF-binding properties of both Tbps, in contrast with previously reported methods [15]. TbpA, TbpB and TbpAjB each bound hTF in solid-and liquid-phase assays.…”
Section: Discussionmentioning
confidence: 95%
“…The interaction between isolated meningococcal Tbps and hTF has been quantitatively characterized for the first time. This has been possible for individual TbpA and TbpB due to the development of a novel purification procedure which preserved the hTF-binding properties of both Tbps, in contrast with previously reported methods [15]. TbpA, TbpB and TbpAjB each bound hTF in solid-and liquid-phase assays.…”
Section: Discussionmentioning
confidence: 95%
“…For N. meningitidis, it was found that the TbpB proteins could be separated into two families based on sequence and antigenicity (28); however, there are common antigenic domains in the TbpB proteins from N. meningitidis, N. gonorrhoeae, H. influenzae, and A. pleuropneumoniae (17,33). Furthermore, TbpBs from N. meningitidis, H. influenzae, and A. pleuropneumoniae have been demonstrated to be protective antigens in various animal challenge models (1,21,22,29).…”
mentioning
confidence: 99%
“…One concern in view of the findings of a previous study [8]using co‐purified TbpA+B was that separation of the proteins to individual TbpA and TbpB had resulted in reduced antigenicity. Unlike the study of Lissolo et al [6], all the separate Tbps used here retained their ability to bind transferrin. Responses to separated TbpA and the co‐purified TbpA+B had high correlation coefficients suggesting that the proportion of antibody positive and negative sera remained the same.…”
Section: Discussionmentioning
confidence: 70%
“…These proteins are expressed by all meningococci and are thought to be involved in iron acquisition from transferrin. They have been shown to elicit protective and bactericidal antibodies to the homologous meningococcal strain in laboratory animals [5, 6]. TbpB has been shown to exhibit antigenic heterogeneity in laboratory animals possibly limiting its vaccine potential [7].…”
Section: Introductionmentioning
confidence: 99%